Solve for j -2(j-3)=-2j+6

Math
-2(j-3)=-2j+6
Simplify -2(j-3).
Tap for more steps…
Apply the distributive property.
-2j-2⋅-3=-2j+6
Multiply -2 by -3.
-2j+6=-2j+6
-2j+6=-2j+6
Move all terms containing j to the left side of the equation.
Tap for more steps…
Add 2j to both sides of the equation.
-2j+6+2j=6
Combine the opposite terms in -2j+6+2j.
Tap for more steps…
Add -2j and 2j.
0+6=6
Add 0 and 6.
6=6
6=6
6=6
Since 6=6, the equation will always be true for any value of j.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for j -2(j-3)=-2j+6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top